Novel SLC22A16 polymorphisms and influence on doxorubicin pharmacokinetics in Asian breast cancer patients. (June 2007) - Lal, Suman; Wong, Zee Wan; Jada, Srinivasa Rao; Xiang, Xiaoqiang; Chen Shu, Xiao; Ang, Peter Cher Siang; Figg, William D; Lee, Edmund JD; Chowbay, Balram
Objective: To identify novel polymorphisms in the solute carrier SLC22A16 gene and determine their influence on the pharmacokinetics of doxorubicin and doxorubicinol in Asian breast cancer patients.Methods: SLC22A16 coding regions were screened in a total of 400 healthy subjects belonging to three distinct Asian ethnic groups (Chinese [n = 100], Malays [n = 100] and Indians [n = 100]) and in the Caucasian population (n = 100). Pharmacokinetic parameters of doxorubicin and doxorubicinol were estimated in Asian breast cancer patients undergoing adjuvant chemotherapy to investigate genotype––phenotype correlations.Results: Four novel polymorphisms (c.146A>G [exon 2], c.312T>C, c.755T>C [exon 4] and c.1226T>C [exon 5]) were identified. The genotypic frequency of the homozygous c.146GG polymorphism was approximately twofold higher in the healthy Chinese (13%) & Malay (18%) populations compared with the Indian (7%) and Caucasian (9%) populations. The genotypic frequency of the c.1226T>C polymorphism was observed to be significantly higher among the Caucasian (11%) and Indian (8%) study subjects compared with the Chinese (1%) and Malay (1%) ethnic groups (p < 0.005 in each case). Breast cancer patients harboring the 146GG genotype showed a trend towards higher exposure levels to doxorubicin (AUC0––∞∞ /dose/body surface area [BSA] [hm -5 ]: 21.6; range: 18.8––27.7) compared with patients with either the reference genotype (AUC0––∞∞ /dose/BSA[hm -5 ]: 17.4; range: 8.2––26.3, p = 0.066) or heterozygotes (AUC0––∞∞ /dose/BSA[hm -5 ]: 15.4; range: 6.2––38.0, p = 0.055). The exposure levels of doxorubicinol were also higher in patients harboring the variant 146GG genotype (AUC0––∞∞ /dose/BSA[hm -5 ]: 13.3; range: 8.8––21.7) when compared with patients harboring the reference genotype (AUC0––∞∞ /dose/BSA[hm -5 ]): 9.8; range: 6.1––24.3, p = 0.137) or heterozygotes (AUC0––∞∞ /dose/BSA[hm -5 ]: 8.98; range: 3.7––20.6, p = 0.047).Conclusion: Among the four novel SLC22A16 polymorphisms identified, the c.146A>G and c.1226T>C polymorphisms exhibited interethnic variations in allele and genotype frequencies. This exploratory study suggests that the c.146A>G variation could contribute to the variations in the pharmacokinetics of doxorubicin and doxorubicinol in Asian cancer patients. Further in vitro studies are required to determine the functional impact of these novel polymorphisms on doxorubicin pharmacokinetics in cancer patients.